Heat Capacity of Various (Solvent+Terpene) Mixtures as Function of Composition and Temperature (2023)
ABSTRACT: The heat capacity of diferent mixtures of terpenes (α-pinene, β-pinene, limonene oxide) and solvents (acetone, toluene, ethyl acetate) at atmospheric pressure (85.1 kPa atm in Medellin, Colombia) were measured using a microcalorimeter at several terpene molar fractions and from room temperature to a value close to the solvent boiling point. The mixtures analyzed were acetone+α-pinene from 298.15 to 323.15 K, toluene+limonene oxide and toluene+β-pinene from 298.15 to 358.15 K, and ethyl acetate+β-pinene between 298.15 and 338.15 K. These mixtures, at the selected temperature ranges, are used in fnechemical catalytic reactions. The experimental heat capacity values were ftted to polynomials as a function of temperature. Excess heat capacity was calculated with the measured molar heat capacity for all the mixtures, it decreased with temperature. Experimental uncertainty was less than 1.5% with a confdence level of 95% using k=2. The experimental results were consistent, for example the heat capacity of ethyl acetate+β-pinene mixture increased as the temperature increased and decreased with the composition of the solvent; at 308.15 K the heat capacity decreased from 252.73 to 245.17 J mol−1 K−1 when solvent composition increased from 0.1546 to 0.2797 and at a solvent composition of 0.1546, heat capacity increased from 237.26 to 252.73 J·mol−1·K−1 when temperature increased from 298.15 to 308.15 K.